2007
DOI: 10.1007/s10551-007-9538-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Behaviour of Tertiary Education Students in Cyprus

Abstract: Cyprus, tertiary education, students ethical standing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
2
28
0
1
Order By: Relevance
“…The conclusion that there exists a negative relationship between business ethics and an entrepreneurial interest lends support to the anxiety of ethicist and the like about the ethical standards of business students and other future professionals in corporate and financial positions (Lane and Schaupp 1989;McCabe et al 1991;McCabe 2001;Zopiatis and Krambia-Kapardis 2007). The problem seems to be especially grave for professions in the financial sector.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The conclusion that there exists a negative relationship between business ethics and an entrepreneurial interest lends support to the anxiety of ethicist and the like about the ethical standards of business students and other future professionals in corporate and financial positions (Lane and Schaupp 1989;McCabe et al 1991;McCabe 2001;Zopiatis and Krambia-Kapardis 2007). The problem seems to be especially grave for professions in the financial sector.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, scholars also attribute responsibility to colleges and universities to counteract or even prevent the development of unethical attitudes and behaviours of their students (Felton and Sims 2005;Lane et al 1988;Lysonski and Gaidis 1991). Zopiatis and Krambia-Kapardis (2007) even formulate a number of practical real-world measures that could be taken by educational institutions in order to stimulate ethical behaviour of their students. In doing so they suggest that the development of ethical attitudes and behaviour can best be understood as an educational socialisation process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zopiatis and Krambia-Kapardis (2008) note that prior to their study, no research into the ethical judgments of students in tertiary education had been conducted in the Republic of Cyprus. Thus the area of study reported in this paper is new both in its exploration of student attitudes towards ethics in these countries and the possible link to national culture.…”
Section: National Culture and Ethicsmentioning
confidence: 99%